Harnessing Biotechnology for Life Sciences Research: Innovations in Genetic Engineering, Bioinformatics, and Environmental Biotechnology - Fattah , Noorsan Taajeel; shawkat , Sebal fıkrat; Sakban , Ali Karim; Saber , Esra Higran; Fayyad , Zainab Mahmoud (American Journal of Biology and Natural Sciences, 2025)
The revolution in Life Sciences research (LSR) has been made possible by the availability of state-of-the-art, high-throughput and high-resolution biochemical, biophysical, structural and sequencing techniques. The LSR community requires a new generation of scientific instrumentation that can meet this demand. Such equipment requires specialized skills, fine-tuning and constant repairs, thus demanding an enormous burden from LSR laboratories. The LSR community needs to be freed from these non-scientific tasks so that scientists can concentrate on the science. Unfortunately, in many cases such high-end equipment is not readily available to life scientists, for example in mid-tier LSR laboratories of developing countries. Countries such as Brazil or Russia are trying to ameliorate this situation by investing billions into cutting-edge LSR techniques in mega-facilities such as synchrotrons or free electron lasers. In this case access is very limited; not to mention travel expenses for researchers from many countries having no free access to Brazilian or Russian mega-facilities. Modern research broadly depends on state-of-the-art high-end equipment. In LSR these are MRIs, X-ray diffractometers, electron or atomic-force microscopes, mass-spectrometers, sequencing machines, etc., which give rise to enormous amounts of data requiring specialized analysis and interpretation. These techniques are not just machines and methodologies, they are scientific instrumentation, which demands specialized skills to be operated and maintained. As a rule, such high-end equipment is expensive, energy-consuming, in need of constant maintaining and tuning, which place a huge burden on laboratories. Biophysics, structural biology, and broadly biochemistry are disciplines needing such advanced instrumentation to provide the necessary information about structure and dynamics of biological objects involved in life processes, e.g. proteins. Some groups are trying to meet this demand by developing scientific instrumentation in home laboratories instead of commercially immobilized devices.